The Role of Training Effectiveness in Enhancing Online Teaching Competence and Professional Development: A SEM Approach - Abidi, S. M. Kaunain; Ishrat, Azra; Siddiqui, Masood H.; Singh, Anjali; Ali, Shagufta; Ali, Naghma (International Review of Management and Marketing, 2026)
This study examines the role of training effectiveness in enhancing online teaching competence and professional development among educators, addressing the growing demands of digital education. Using a quantitative research design, data were collected from 603 in-service teachers in India and analyzed through Structural Equation Modeling. The study explores how individual, learning, and organizational performance outcomes of training influence professional development via the mediating role of online teaching competence. Findings revealed that individual and organizational performance positively predicted online teaching competence, with organizational performance exerting the strongest influence. Conversely, learning performance showed a slight negative relationship, suggesting gaps between theoretical training and practical application. Online teaching competence significantly enhanced all dimensions of professional development, emphasizing its pivotal role in sustaining educators’ growth. The study highlights the need for practice-oriented, contextually relevant training and institutional support mechanisms to empower digitally competent educators and promote inclusive, adaptive, and high-impact online teaching practices.